2008
DOI: 10.1111/j.1365-2966.2008.13850.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-common envelope binaries from SDSS - III. Seven new orbital periods

Abstract: We present follow‐up spectroscopy and photometry of 11 post‐common envelope binary (PCEB) candidates identified from multiple Sloan Digital Sky Survey (SDSS) spectroscopy in an earlier paper. Radial velocity measurements using the Na i λλ8183.27, 8194.81 absorption doublet were performed for nine of these systems and provided measurements of six orbital periods in the range Porb= 2.7– 17.4 h. Three PCEB candidates did not show significant radial velocity variations in the follow‐up data, and we discuss the imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Counting the SDSS sample with 3 200 systems and the LAMOST sample with 900 objects, both catalogues have been prolific at revealing a large number of radial velocity variable, i.e. PCEBs, and non-variable systems (Rebassa-Mansergas et al 2007, 2011Schreiber et al 2008Schreiber et al , 2010 -and the corresponding orbital period distributions (Rebassa-Mansergas et al 2008;Nebot Gómez-Morán et al 2011) -as well as of eclipsing binaries (Parsons et al 2012(Parsons et al , 2013(Parsons et al , 2015Pyrzas et al 2009Pyrzas et al , 2012Rebassa-Mansergas et al 2016a, 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…Counting the SDSS sample with 3 200 systems and the LAMOST sample with 900 objects, both catalogues have been prolific at revealing a large number of radial velocity variable, i.e. PCEBs, and non-variable systems (Rebassa-Mansergas et al 2007, 2011Schreiber et al 2008Schreiber et al , 2010 -and the corresponding orbital period distributions (Rebassa-Mansergas et al 2008;Nebot Gómez-Morán et al 2011) -as well as of eclipsing binaries (Parsons et al 2012(Parsons et al , 2013(Parsons et al , 2015Pyrzas et al 2009Pyrzas et al , 2012Rebassa-Mansergas et al 2016a, 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, if no RV variation is detected from spectra taken separated by at least one night, the system is considered as a likely wide binary candidate that presumably evolved avoiding episodes of mass transfer. We fit the Na I λλ 8183.27, 8194.81 absorption doublet with a second-order polynomial plus a double-Gaussian line profile of fixed separation, while the Hα emission line (if present in the spectrum) is fitted with a second-order polynomial plus a single-Gaussian line profile (Rebassa-Mansergas et al 2008;Ren et al 2013). With the aim of increasing the SN ratio, the final released LAMOST DR5 spectra are the result of combining several different sub-exposure spectra (hereafter sub-spectra).…”
Section: Identification Of Close Wdms Binariesmentioning
confidence: 99%
“…It has to be noted that the higher PCEB fraction derived by analysing the Hα RVs needs to be taken with caution. This is because Hα RVs are less robust for detecting RV variations due to magnetic activity effects (Rebassa-Mansergas et al 2008).…”
Section: Identification Of Close Wdms Binariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been shown that the early sample of well studied PCEBs is not only small but, being drawn mainly from "blue" quasar surveys, it is also heavily biased towards young systems with low-mass secondary stars (Schreiber & Gänsicke, 2003). However, the SDSS (Frieman et al, 2008;Abazajian et al, 2009) has allowed to identify a large number of WD+MS binaries (Heller et al, 2009;Rebassa-Mansergas et al, 2013), and a dedicated radial velocity survey among them has provided the so far largest and most homogeneous sample of close compact binaries with available orbital periods (Rebassa-Mansergas et al, 2008;Nebot Gómez-Morán et al, 2011). Hence, studying the populations of WD+MS binaries that have undergone a common envelope episode it is essential since the distribution of orbital periods and other characteristics of the populations, like the distributions of primary and secondary masses, can be used to constrain the values of the free parameters of the theory of common envelope evolution.…”
Section: Introductionmentioning
confidence: 99%